2024
DOI: 10.2174/2772432817666220512112913
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Hesitancy: A Review of the Literature and Recommendations

Abstract: Vaccines are important to improve immunity against pathogens and diseases. The current COVID-19 disease is rapidly evolving and spreading among people; therefore, it is important to utilize a proper vaccination strategy against it. Currently, many approved vaccines are available and accessible; however, there is a reported hesitancy against taking them among the public and even the health care workers. Mainly, this is attributed to the fear of the possible side effects and complications. Moreover, inaccurate k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…African Americans have medical distrust caused by racial discrimination and had a low probability of receiving the COVID-19 vaccine [21,22]. According to various reports, approximately 40% of the general population had negative views about COVID-19 vaccine [19,23,24]. Lin et al argued that one of the underlying factors that can explain this attitude is the perception that vaccines are unsafe [10].…”
Section: Discussionmentioning
confidence: 99%
“…African Americans have medical distrust caused by racial discrimination and had a low probability of receiving the COVID-19 vaccine [21,22]. According to various reports, approximately 40% of the general population had negative views about COVID-19 vaccine [19,23,24]. Lin et al argued that one of the underlying factors that can explain this attitude is the perception that vaccines are unsafe [10].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence and dissemination of a relatively secure vaccine against COVID-19s has been a major development in the COVID-19 epidemic fight. However, there is indeed a heated debate over whether the vaccine against COVID-19 should be administered to children and young adults [ [1] , [2] , [3] ]. The knowledge, wellness, and very well being of society are all at stake [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study has examined the factors that influence hesitancy toward the second booster of the COVID-19 vaccine among elderly people from residential care homes. Some recent reviews have highlighted factors frequently reported as influencing vaccine booster uptake [ 25 , 26 , 27 ]. Factors investigated include demographics of which age has been found to be more relevant in the context of vaccine booster hesitancy.…”
Section: Discussionmentioning
confidence: 99%